Kepraktisan LKPD “Aku Bisa Membaca dan Menulis” untuk Mengukur Literasi Dasar Siswa Slow Learner - Syifa Kifayatus Sa’diyah; Nurul Istiq’faroh; Dhini Dwi Permatasari (Journal of Contemporary Issues in Primary Education, 2026)
Basic literacy is an essential competency that must be mastered by elementary school students. However, its development remains a challenge, especially for slow learners who have limitations in processing information. One factor that influences learning success is the availability of teaching materials that are appropriate to student characteristics. This study aims to describe the practicality level of the Student Worksheet (LKPD) "I Can Read and Write". This LKPD is used as an instrument to identify the basic literacy of slow learner students in inclusive elementary schools. This study uses a Research and Development (R&D) approach with the ADDIE model. The research subjects consisted of a first-grade teacher at SDN Ketintang II as the practicality assessor and one slow learner student as the interview respondent. Data were collected through a practicality questionnaire and interviews. Data analysis was conducted using descriptive quantitative and qualitative methods. The results showed that the LKPD obtained a practicality percentage of 88%, categorized as very practical. LKPD is considered easy to use, appropriate to student needs, and able to increase learning engagement. Thus, this LKPD has the potential to be an adaptive teaching material as well as an effective basic literacy identification tool.